Choosing the right type of serum for different applications of human adipose tissue-derived stem cells: influence on proliferation and differentiation abilities - Köllensperger, Eva; Bollinger, Nils Michael; Dexheimer, Verena; Gramley, Felix; Germann, Günter; Leimer, Uwe (Cytotherapy, 2014)
Background aims - Adipose tissue-derived stem cells (ADSCs) are thought to have great potential in regenerative medicine. A xenoprotein-free culture and handling system is desirable. To date, there is only little and contradictory information about the influence of the different types of human serum on ADSC proliferation and differentiation. - Methods - First, ADSCs were cultured in media containing regular human serum (HS plus) or fetal calf serum (FCS plus) with supplementation of growth factors for three passages. During passage 4, ADSC proliferative activity and adipogenic, osteogenic and chondrogenic differentiation ability was quantified. Second, ADSCs were cultured with three different human sera (regular human serum [HS], human serum from platelet-poor plasma [SPPP] or human serum from platelet-rich plasma [SPRP]) without supplementation of platelet-derived growth factor and assessed accordingly. The growth factor content of the different types of human sera was determined by means of multiplex protein assay and enzyme-linked immunosorbent assay. - Results - The different sera did not affect ADSC doubling time significantly (P < 0.05). Specific glycerol-3-phosphat-dehydrogenase activity was significantly lower in cultures with SPRP (P < 0.01) compared with the other media compositions. Extracellular calcium deposition was significantly higher in cells differentiated in cultures with HS or SPPP compared with those with SPRP, HS plus or FCS (P < 0.01). Glycosaminoglycan content and collagen 2 were highest in cells cultured with SPRP (P < 0.001). - Conclusions - Culturing ADSCs in human serum appears to be a reasonable and efficient alternative compared with FCS. With respect to the outcome of a sighted clinical application, it appears to be feasible to handle the cells in a serum suitable for the intended later use.